The Power of Color: A Case Series. - Esposito, Christina (Optometry & Visual Performance, 2014)
Background: The use of colored light, filters, and therapeutic tinting dates back to the early years of optometry. It has been used by optometrists and other professionals throughout history for a variety of different reasons, including photophobia, near point stress, migraines, and dyslexia. Case Series: A series of cases are presented where color is used to help patients resolve their visual disturbances. The patients who were identified are those suffering from photophobia, reading difficulties, and visual changes related to a vestibular condition. The colors are chosen using the Intuitive Colorimeter. This instrument is used to investigate the possible preferences for a specific color to reduce the patient's symptomatology. This is done logically and sequentially to explore color space in order to find the optimal precision tint for the relief of perceptual distortions. Discussion: Tinting contact lenses and/or glasses for therapeutic reasons can be time consuming but can be a rewarding experience for both the clinician and the patient.